Perinatal Opioid Exposure Primes the Peripheral Immune System Toward Hyperreactivity - Newville, Jessie; Maxwell, Jessie R.; Kitase, Yuma; Robinson, Shenandoah; Jantzie, Lauren L. (Frontiers in Pediatrics, 2020)
The increased incidence of opioid use during pregnancy warrants investigation to reveal the impact of opioid exposure on the developing fetus. Exposure during critical periods of development could have enduring consequences for affected individuals. Particularly, evidence is mounting that developmental injury can result in immune priming, whereby subsequent immune activation elicits an exaggerated immune response. This maladaptive hypersensitivity to immune challenge perpetuates dysregulated inflammatory signaling and poor health outcomes. Utilizing an established preclinical rat model of perinatal methadone exposure, we sought to investigate the consequences of developmental opioid exposure on in vitro activation of peripheral blood mononuclear cells (PBMCs). We hypothesize that PBMCs from methadone-exposed rats would exhibit abnormal chemokine and cytokine expression at baseline, with exaggerated chemokine and cytokine production following immune stimulation compared to saline-exposed controls. On postnatal day (P) 7, pup PMBCs were isolated and cultured, pooling 3 pups per n. Following 3 and 24 hours, the supernatant from cultured PMBCs was collected and assessed for inflammatory cytokine and chemokine expression at baseline or LPS stimulation using multiplex electrochemiluminescence. Following 3 and 24 hours, baseline production of pro-inflammatory chemokine and cytokine levels were significantly increased in methadone PBMCs (p<0.0001). Stimulation with LPS for 3 hours resulted in increased TNF and CXCL1 expression by 3.5-fold in PBMCs from methadone-exposed PBMCs compared to PBMCs from saline-exposed controls (p<0.0001). PBMC hyperreactivity was still apparent at 24 hrs of LPS stimulation, evidenced by significantly increased TNF, CXCL1, IL-6, and IL-10 production by methadone PMBCs compared to saline control PBMCs (p<0.0001). Together, we provide evidence of increased production of pro-inflammatory molecules from methadone PBMCs at baseline, in addition to sustained hyperreactivity relative to saline-exposed controls. Exaggerated peripheral immune responses exacerbates inflammatory signaling, with subsequent consequences on many organ systems throughout the body, such as the developing nervous system. Enhanced understanding of these inflammatory mechanisms will allow for appropriate therapeutic development for infants who were exposed to opioids during development. Furthermore, these data highlight the utility of this in vitro PBMC assay technique for future biomarker development to guide specific treatment for patients exposed to opioids during gestation.